Sensorial investigations : a history of the senses in anthropology, psychology, and law - Howes, David, 1957- (Perspectives on sensory history., 2023)
"Presents a history of the senses in the fields of anthropology, psychology, and law, identifying important shifts and key disciplinary concerns"--